The Extent of Application of Good Governance at Qatar University from the Point of View of Heads of Academic Departments and Faculty Members - Hamda Al- Saa'deyah (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to identify the degree of application of good governance at Qatar University from the point of view of the heads of academic departments and faculty members. Its sample consisted of (318) faculty members and heads of academic departments at Qatar University. The researcher used a descriptive approach by developing a study tool (a questionnaire) to measure the degree of application of good governance, consisting of (42) items. The study concludes that the degree of application of good governance at Qatar University from the point of view of the study sample as a whole was very high in general. The study also revealed that there were statistically significant differences at (0.05) in the degree of application of good governance at Qatar University from the point of view of the study sample members, due to the variable of gender in favor of males, the variable of academic rank in favor of an assistant professor, the variable of job and in favor of heads of academic departments, and the variable of years of work at Qatar University in favor of the 1-5 range. In light of the results, the study recommends active participation with the heads of academic departments and members of the faculty in making decisions and regulations.